2015
DOI: 10.1073/pnas.1517033112
|View full text |Cite
|
Sign up to set email alerts
|

Lnx2 ubiquitin ligase is essential for exocrine cell differentiation in the early zebrafish pancreas

Abstract: The gene encoding the E3 ubiquitin ligase Ligand of Numb protein-X (Lnx)2a is expressed in the ventral-anterior pancreatic bud of zebrafish embryos in addition to its expression in the brain. Knockdown of Lnx2a by using an exon 2/intron 2 splice morpholino resulted in specific inhibition of the differentiation of ventral bud derived exocrine cell types, with little effect on endocrine cell types. A frame shifting null mutation in lnx2a did not mimic this phenotype, but a mutation that removed the exon 2 splice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…In earlier studies we found that the lnx2a gene is required for the differentiation of exocrine cells in the pancreas of zebrafish embryos [19]. During these studies we felt that it would be desirable to delete almost the entire lnx2a gene, a segment of about 29 kb, and replace it with a donor cassette that could assist in future studies of the locus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In earlier studies we found that the lnx2a gene is required for the differentiation of exocrine cells in the pancreas of zebrafish embryos [19]. During these studies we felt that it would be desirable to delete almost the entire lnx2a gene, a segment of about 29 kb, and replace it with a donor cassette that could assist in future studies of the locus.…”
Section: Resultsmentioning
confidence: 99%
“…The donor cassette was flanked by homology arms of about 1 kb on the 5’ and 3’ sides, as suggested by Zu et al, 2013 [11]. We used the previously described TALEN pair, found to be efficient in generating deletions in the lnx2a gene [19], to create a double stranded break in the locus to stimulate recombination. In addition we introduced reagents designed to inhibit nonhomologous end joining (NHEJ) and to stimulate homologous recombination, as suggested by Qi et al and Panier and Boulton [22,23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The donor cassette was flanked by homology arms of about 1 kb on the 5' and 3' sides, as suggested by Zu et al, 2013 [11]. We used the previously described TALEN pair, found to be efficient in generating deletions in the lnx2a gene [19], to create a double stranded break in the locus to stimulate recombination. In addition we introduced reagents designed to inhibit nonhomologous end joining and to stimulate homologous recombination, as suggested by Qi et al and Panier and Boulton [22,23].…”
Section: Resultsmentioning
confidence: 99%